A PROSPECTIVE STUDY ON IMPACT OF PATIENT COUNSELLING ON QUALITY OF LIFE AND MEDICATION ADHERENCE IN EPILEPTIC PATIENTS - P, Ayswarya; s, Sathesh Kumar (Asian Journal of Pharmaceutical and Clinical Research, 2017)
Objective: To study the impact of patient counseling on medication adherence and quality of life (QOL) in epileptic patients and to assess the factors affecting medication adherence. Methods: This study is a prospective observational study involving 100 patients with an age limit of 8-60 years and those taking Antiepileptic drugs for at least 3 months. The study population received patient counseling during their first visit. The impact of patient counseling on QOL and medication adherence was assessed using self-reported questionnaire QOLIE-31 and MMAS-8 between the first visit and the second visit. Statistical analysis (Paired t-test and Paired Chi-square test) was performed to analyze the impact of patient counseling on QOL and medication adherence in epileptic patients. Results: A total of 100 patients were included in the study. After providing patient counseling, it was observed that there was a statistically significant (p<0.05) improvement in all domains of QOLIE-31 and MMAS-8 scores. Before counseling, mean overall T-score of QOLIE-31 was 44.08±2.07which was changed to 49.14±1.27 after patient counseling with a mean change of 5.06 in overall T-score. In the case of medication adherence, before counseling 77% subjects were nonadherent to therapy, after counseling it was reduced to 41%. The common reasons for medication adherence were forgetfulness, unawareness, therapy related, and economics related. Out of which forgetfulness along with unawareness was the major one. Conclusion: The study described that patient counseling plays a major role in improving QOL and medication adherence. Keywords: QOLIE-31, MMAS-8, Epilepsy, Antiepileptic drugs, Patient counseling.